Consumer's scepticism of wine awards: A study of consumers' use of wine awards. (March 2017) - Neuninger, Rosemarie; Mather, Damien; Duncan, Tara
Abstract: This study aims to explain the process by which the effect of wine awards, as an extrinsic cue, becomes the reverse of what was intended. Based on their age and commercial background, and separating those with professional affiliations, participants were placed into one of four focus groups. Thematic analysis was applied to focus groups. Most consumers are found to be sceptical about wine awards and critical of awards, as confusing and misleading. Most consumers also criticised the transparency of the awards process. Despite this, participants frequently used awards for evaluating wines. Decision-making theory (Pellemans, 1971) needs extending to include awards.